Association between early coagulation disorders and the risk of severe acute kidney injury in traumatic brain injury patients: a retrospective cohort study using the MIMIC-IV database - Gao, Yu; Li, Yong; Zhou, Hai; Wang, Xin; Wang, Guojun; Zhu, Lin (Frontiers in Neurology, 2025)
AimAcute kidney injury (AKI) and coagulation disorders are two common complications of traumatic brain injury (TBI) that are associated with poor prognosis. However, the relationship between early coagulation disorders and the risk of severe AKI in TBI patients remains unclear. This study aimed to explore the association between early coagulation disorders and the risk of severe AKI in TBI patients admitted to the intensive care unit (ICU).MethodsIn this retrospective cohort study, adults diagnosed with TBI were selected from the Medical Information Mart for Intensive Care (MIMIC)-IV database. The outcome was the risk of severe AKI within 7 days of ICU admission in TBI patients. Covariates including sociodemographic information, vital signs, scoring systems, and laboratory parameters were extracted from the database. Univariable and multivariable Cox proportional hazard regression models were used to assess the association between early coagulation disorders and the risk of severe AKI within 7 days of admission to the ICU in TBI patients. Subgroup analyses based on age and the Glasgow Coma Scale (GCS) score were further conducted to assess the association.ResultsA total of 846 patients were finally included, of whom 187 (22.10%) had severe AKI. After adjusting for all covariates, the TBI patients with early coagulation disorders had a higher risk of developing severe AKI within 7 days of ICU admission compared to the TBI patients without early coagulation disorders (hazard ratio (HR) = 1.40, 95% confidence interval (CI): 1.04–1.89), particularly among those aged ≥65 years (HR = 1.46, 95%CI: 1.01–2.04) and those with a GCS score ≤ 13 (HR = 1.91, 95%CI: 1.16–3.15).ConclusionTBI patients with early coagulation disorders had a higher risk of developing severe AKI within 7 days of ICU admission. This may serve as a promising biomarker and could be helpful for managing kidney health in TBI patients.